The reliability of hearing implants: report on the type and incidence of cochlear implant failures. (3rd July 2020) - Van de Heyning, Paul; Atlas, Marcus; Baumgartner, Wolf-Dieter; Caversaccio, Marco; Gavilan, Javier; Godey, Benoit; Gstöttner, Wolfgang; Hagen, Rudolph; Yongxin, Li; Karltorp, Eva; Kameswaran, Mohan; Kuzovkov, Vlad; et al.
Abstract : Objectives: This study presents the data collected through a database on the type and incidence of cochlear implant device failures and major complications and quantifies the risk of failures across time based on the Association for the Advancement of Medical Instrumentation (AAMI) CI86:2017 standard. Methods: Information on reliability of MED-EL cochlear implants was collected from the MED-EL complaint database between 2003 and2013. Explants were categorized and device reliability was calculated according to the AAMI CI86:2017 standard principles. Results: Data were collected for 11662 devices (5462 children, 6200 adults). The mean duration of follow up was 46.16 months. The total failure rate for all devices and all subjects was 2.41%. Medical related explants (MRE) were significantly worse for children than for adults with the ceramic implants, C40+ ( p = 0.008) and PULSAR ( p = 0.020). Device failure explants (DFE) were significantly worse for children than for adults with all four devices in the study, the C40+ ( p < 0.001), PULSAR ( p < 0.001), SONATA ( p < 0.001), and CONCERTO ( p = 0.023). The mean annual failure rate for all subjects and devices was 0.63% (1.03% for children, 0.28% for adults). The mean annual failure rate was 0.90% for the C40+; 0.57% for the PULSAR; 0.46% for the SONATA; and 0.39% for the CONCERTO. Conclusions: Compared to adults, children had significantly worse MRE and DFE due to a higher risk of head trauma and more vulnerable skull anatomy. Further, the authors conclude that the AAMI standard will ensure a more comprehensive and transparent evaluation of cochlear implant reliability in the future.